Perancangan Electronic Supply Chain Management (E-SCM) pada PT. Indofood CBP Sukses Makmur TBK - Paramita Citra Indah Mulia; Muhamad Farid; Evy Nurmiati (Yayasan Literasi Sains Indonesia, 2022)
PT. Indofood CBP Sukses Makmur TBK is a company engaged in the Fast Moving Consumer Good (FMCG) sector. The company has a comprehensive market coverage in Indonesia and the global market. Supply chain management has an important role in maximizing supply chain activities from suppliers to consumers at PT. Indofood CBP Sukses Makmur TBK. PT. Indofood CBP Sukses Makmur TBK has supply chain problems such as changing levels of consumer demand that affect the amount of raw materials needed, warehouse problems, data errors, and communication which form the basis for the need for e-SCM development to improve the overall effectiveness of the supply chain management process at this company. . The design of e-SCM at PT. In this research, Indofood CBP Sukses Makmur TBK uses a literature study with Object Oriented Analysis Design Steps from the results of the company's readiness to implement e-SCM according to Ross, namely Energize the Organization, Enterprise Vision, Supply Chain Value Assessment, Opportunity Identification, and Strategy Decision. In this design, the researchers designed a rich picture, use case diagram, activity diagram, and user interface in the e-SCM application. The designed e-SCM application is able to integrate data and information in the process of delivering raw materials to finished products involving seven actors, namely procurement, suppliers, material warehouse admins, production, product admins, distributors, and consumers, so as to increase the overall effectiveness of the SCM process. on the company.